Fundamentals of polymer physics and molecular biophysics - Bohidar, Himadri B. (Cambridge : Cambridge University Press, 2015)
Macromolecules in solutions can be distinctly characterised by their transport behaviour in solution phase. The study of the transport processes includes diffusion coefficient, sedimentation coefficient, intrinsic viscosity and friction constant. The question arises as to how to explicitly characterise the macromolecules from the data of coefficients. This book answers this question in a systematic manner. It provides physical interpretation of the data obtained in macromolecular transport phenomena in a given system and also addresses some important issues and concepts related to biopolymers such as proteins and nucleic acids. The application of concepts like conformational properties and salient physicochemical features of protein and nucleic acids is also elucidated in the book. Based on the molecular structure, it provides the essential concepts which can be used to model and analyse the static and transport behaviour of polymers and biopolymers.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Polymers; Physics; Biophysics